The Roles of microRNAs in Regulating Chemotherapy Resistance of Non-Small Cell Lung Cancer - Wei, Xiaoxuan; Shen, Xiaoyan; Ren, Yanchen; Hu, Weidong (Current Pharmaceutical Design, 2017)
Lung cancer is considered the leading cause of cancer death in the word. Among all lung cancer cases, non-small cell lung cancer (NSCLC) accounts for 85%. Currently, chemotherapy is still the major therapeutic method of lung cancer. However, chemoresistance is a serious obstacle in treating NSCLC. Up to now, many reports have suggested that microRNAs(miRNAs) could contribute to lung cancer cell chemosensitivity. MicroRNAs, a class of endogenous non-coding small RNAs, regulate gene expression by binding to their complementary target messenger RNAs, leading to mRNA degradation or translational suppression. Numerous studies indicate that changes of specific miRNA expression may contribute to chemoresistance or chemosensitivity. Consequently, targeting specific miRNAs could become an effective approach to predict the therapeutic effect of different anticancer agents, achieve more effective personalised treatments and enhance chemosensitivity. This review summarizes the several major drug resistance mechanisms and focuses on the roles of miRNAs in regulating chemoresistance in NSCLC.
Keywords: MicroRNAs